Investigating the Human-M. tuberculosis interactome to identify the host targets of ESAT-6 and other mycobacterial antigens - Bruiners, Natalie (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.